Vortex-induced vibration characteristics of multi-mode and spanwise waveform about flexible pipe subject to shear flow - Bao, Jian; Chen, Zheng-Shou (International journal of naval architecture and ocean engineering, 2021)
Numerical simulations of the Vortex-Induced Vibration (VIV) about a large-scale flexible pipe subject to shear flow were carried out in this paper. Efficiency verification was performed firstly, validating that the proposed fluid–structure interaction solution strategy is competent in predicting the VIV response. Then, the VIV characteristics related to multi-mode and spanwise hybrid waveform about the flexible pipe attributed to shear flow were investigated. When inflow velocity rises, higher vibration modes are apt to be excited, and the spanwise waveform easily convertes from a standing-wave-dominated status to a hybrid standing–traveling wave status. The multi-mode or even multiple-dominant-mode is prone to occur, that is, the dominant mode is often followed by several apparent subordinate modes with considerable vibration energy. Hence, the shedding frequencies no longer obey Strouhal law, and vibration trajectories become intricate. According to the motion analysis concerning the coupled cross-flow and in-line vibrations, as well as the corresponding wake patterns, a tight coupling interaction exists between the structural deformation and the wake flow behind the flexible pipe. In addition, the evolution of the vortex tube along the pipe span and a strong 3D effect are observed due to the slenderness of the flexible pipe and the variability of the vortex shedding attributed to the shear flow.